Pengaruh Prinsip Etika Bisnis Terhadap Peningkatan Perekonomian Pedagang Kaki Lima Di Wilayah Kota Blitar - Ellyn Citra Putrantri; Marlena (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2023)
This research was conducted with the aim of knowing the effect of implementing business ethics on improving the economy of street vendors in the City of Blitar. This type of research includes quantitative research. Samples were taken by purposive sampling technique, namely as many as 48 street vendors in the Blitar City area. Data analysis technique using multiple linear regression. The results of the study show that the principle of individual honesty has a significant influence on the economic growth of street vendors. However, the principle of moral integrity individually has a significant influence on the economic growth of street vendors. This study indicates that the principle of justice individually does not have a significant influence on the economic growth of street vendors. However, the principles of honesty, moral integrity and justice together significantly influence the economic growth of street vendors. The results of this study can be used by street vendors in Blitar City to improve the economy through honesty and moral integrity in trading.